An experimental and feasibility study into the response of titanium alloys subjected to compression and MDF tests - Huang, Cindy Xiaohui. (2013)
Titanium and its alloys have proven themselves to be technically superior and cost effective materials when compared to aluminum and steel for a wide range of applications. Despite the high price of titanium, its usage to manufacture many items for aerospace, automotive, marine and military uses is justifiable. The initial high cost is compensated either by the advantages of weight reduction due to the low density of the metal or by the increased life and reliability of the component due to high corrosion resistance of the metal.